The effects of arbuscular mycorrhizal fungal species and taxonomic groups on stressed and unstressed plants: a global meta‐analysis - Marro, Nicolás; Grilli, Gabriel; Soteras, Florencia; Caccia, Milena; Longo, Silvana; Cofré, Noelia; Borda, Valentina; Burni, Magali; Janoušková, Martina; Urcelay, Carlos (The New phytologist, 2022)
Summary The great majority of plants gain access to soil nutrients and enhance their performance under stressful conditions through symbiosis with arbuscular mycorrhizal fungi (AMF). The benefits that AMF confer vary among species and taxonomic groups. However, a comparative analysis of the different benefits among AMF has not yet been performed. We conducted a global meta‐analysis of recent studies testing the benefits of individual AMF species and main taxonomic groups in terms of plant performance (growth and nutrition). Separately, we examined AMF benefits to plants facing biotic (pathogens, parasites, and herbivores) and abiotic (drought, salinity, and heavy metals) stress. AMF had stronger positive effects on phosphorus nutrition than on plant growth and nitrogen nutrition and the effects on the growth of plants facing biotic and abiotic stresses were similarly positive. While the AMF taxonomic groups showed positive effects on plant performance either with or without stress, Diversisporales were the most beneficial to plants without stress and Gigasporales to plants facing biotic stress. Our results provide a comprehensive analysis of the benefits of different AMF species and taxonomic groups on plant performance and useful insights for their management and use as bio‐inoculants for agriculture and restoration.